Phase Field Modelling of Dendrite Fragmentation during Thermal Shock - Guo, Z; Mi, J; Grant, P (2010)
The dendrite grain growth of a succinonitrile based transparent alloy, their fragmentation under an intense thermal shock and the subsequnet morphology evolution during solidification have been simulated using a two-dimensional binary alloy phase field model coupled with heat and solute transfer. The effect of a sudden, rapid change in the thermal environment (thermal shock) was implemented in the model and the resulting effect on the incipient dendritic grain morphology was studied. Thermal shock effectively promoted the fragmentation of the dendritic grains, providing a significant grain multiplication effect to refine the final solidification microstructure. © (2010) Trans Tech Publications.